Investigating the functional and adaptive significance of leaf size and shape variation in Jamesbrittenia (Scrophulariaceae (s.s). tribe Manulae) : an experimental and comparative approach - Moore, Timothy E (Department of Biological Sciences, 2017)
The adaptive significance of variety in leaf forms remains a mystery for many plant groups. This study aimed, using a combined experimental and comparative approach, to investigate the functional significance of leaf size and shape variation, as well as the patterns of leaf form variation in the genus Jamesbrittenia within the context of phylogenetic history. Leaf sizes 63-measured Jamesbrittenia varied between 0.006cm² (in J. microphylla) and 6.52cm² (in J. megaphylla). Correlations between leaf form and the environment suggest leaf size and shape are primarily adapted to water availability, with only leaf dimension being significantly associated with temperature, while, soil fertility shows no relationship with leaf size. Life history is important, however, as broader leaved annuals and species with shorter-lived leaves are associated with more arid habitats. Results of the experimental trials suggest that the primary function leaf size and shape reduction is to reduce water loss, and not to increase heat shedding. While larger leaves transpire more on a leaf-by-leaf basis, transpiration may be higher in broader leaved species at the whole-plant due to higher total plant transpiration. Thus, it is suggested a reduction in leaf size and dimension in Jamesbrittenia is an adaptation to more arid environments. Alternatively, a change in life history may enable a plant to escape harsh periods and capitalise on favourable times. A small- to intermediate-leaved, perennial ancestor is inferred for Jamesbrittenia, which was associated with arid regions in either the summer or winter rainfall regions of southern Africa. Shifts to an annual life history in Jamesbrittenia are associated with a shift to drier habitats, particularly in the arid winter rainfall region of South Africa.